AN ANALYSIS OF THE APPLICATION OF THEME AND THEMATIC PROGRESSION IN STUDENTS' COMMENTARY WRITING - Wahyu, Neneng (2015)
This study aims at discovering how the students of English Education study program organize their writing in term of Theme choice and thematic progressions within the framework of Systemic Functional Linguistics (SFL). In addition, the problems encountered in students' writing also become the concern of this study. The participants of the study are 24 students of English Education study program who have learned Systemic Functional Linguistics. To meet the purposes, the research employs a descriptive-qualitative research design embracing the characteristics of a case study approach. The data were obtained from students' Commentary writing texts and the interview with the students regarding their difficulties during writing process. For the framework of text analysis, this research is grounded by the theory of Systemic Functional Linguistics, especially Theme system proposed by Halliday (1994), Gerot & Wignell (1994), Emilia (2014) Eggins (2004), Bloor and Bloor (1995), Lock (1996) as a tool for analyzing students' text. Twenty four texts were analyzed and four texts were discussed in detail in terms of Theme choice and thematic progression using Systemic Functional Linguistics. The findings reveal that the students employed various types of Theme to make their text coherent, such as unmarked and marked topical Theme, interpersonal Theme, textual Theme, longer unit Theme and predicated Theme. In addition, all types of thematic progression are also found in students' text. Even though the students were quite aware at applying Theme and thematic progression, the researcher still found a problem related to the misuse of Theme and thematic progression; it is the problem of brand new Theme. The problem is influenced either by students' inability to understand the Theme system or teacher' unclear explanation related to the Theme system. The findings of the research suggest that the teachers should provide the explicit and detail teaching of Theme system including Theme and thematic progression. Moreover, the teachers also should apply drafting strategy to eliminate students' errors. Keywords: Systemic Functional Linguistics, Theme, Thematic progression